PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT JMS JAKARTA - NIKEN HERAWATI,; ASRAH TANDIRERUNG RANTEALLO, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Leadership Style is one of the important factor to measure employees job satisfaction. The purpose of this research is to find out the influence of the leadership style toward employees job satisfaction at PT. JMS Jakarta. The method of analyze is using descriptive quantitative with the technique sample is saturated sample and 5% error level with 32 respondent as a sample. The test for this research is using correlation coefficient, determination and linear regression. The result of correlation coefficient is 0,876 which means very strong and from determination test, the result is 76,8% and from linear regression test, got the similarity Y= 12,484 + 0,692X. The conclussion of this research ,there is the significant influences of leadership style to the employees job satisfaction.